Comparison Of Café Atmosphere At Ekopilogi And Ame Coffee - Khoiroh, Novita Zahrotul (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The development of retail stores, especially in the field of food or hangout places, namely cafes in Indonesia, precisely in Sidoarjo, is becoming increasingly interesting to be explored more deeply. This study aims to determine the differences in café atmosphere at Ekopilogi and Ame Coffee. There is one hypothesis in this study, namely café atmosphere. There is a difference between Ekopilogi’s café atmosphere and Ame Coffee’s café atmosphere. Data obtained from distributing questionnaires with non-probability sampling techniques with accidental sampling types, which means an infinite population or spontaneous respondents. The sample taken was 100 respondents from each cafe in Ekopilogi and Ame Coffee, the analysis calculation tool used was SPSS. The results of the data analysis processed are biased data with the value of the variance is 47.147 or less than 50%, which can indicate the absence of common method bias that occurs in the study. In addition, researchers conducted a oneway anova test with that the calculated f value was 34.619. This shows that the calculated f value is greater than the f table value (34.619> 3.89), so the researcher concluded to accept Ha and reject Ho. By accepting Ha, it can be concluded that there are differences in café atmosphere at Ekopilogi and Ame Coffee. there are differences in café atmosphere at Ekopilogi and Ame Coffee. This can be seen from the results of the independent sample T-test test, it can be seen that the probability value of t (sig. 2-tailed) is 0.000 [Sig (2-tailed) <0.05]. So Ho is rejected, meaning that there is a difference in café atmosphere at Ekopilogi and café atmosphere at Ame Coffee. This study is to prove the difference in café atmosphere at Ekopilogi and Ame Coffee, this study used 100 respondents from each cafe with 7 kinds of questionnaires consisting of 7 indicators of café atmosphere with this type of comparative test research using data analysis techniques validity test, reliability test, common method bias test, anova test and independent sample T-test test. The analytical tool used is SPSS version 25 with a confidence level of 0.05.